2022
DOI: 10.2147/ppa.s355891
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Among Patients with Multimorbidity in the United Arab Emirates

Abstract: Background Multimorbidity, defined as having two or more chronic diseases, has a major impact on public health and Sustainable Development Goals (SDG). This study aims to assess the prevalence of medication adherence and associated factors among patients with multimorbidity. Methods A questionnaire-based, cross-sectional survey was conducted by a trained interviewer across patients with multimorbidity attending outpatient clinics in two tertiary referral hospitals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 56 publications
11
17
1
Order By: Relevance
“…In this study, most of the participants were found to have a low level of medication adherence. This finding is consistent with an earlier study [ 38 ], but it is much higher than the other studies [ 14 , 18 , 36 , 39 41 ]. The study findings indicate that a significant proportion of patients with comorbidity fail to achieve the expected adherence level of medications.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, most of the participants were found to have a low level of medication adherence. This finding is consistent with an earlier study [ 38 ], but it is much higher than the other studies [ 14 , 18 , 36 , 39 41 ]. The study findings indicate that a significant proportion of patients with comorbidity fail to achieve the expected adherence level of medications.…”
Section: Discussionsupporting
confidence: 93%
“…Further, the current study also disclosed that patients with a lower number of medications and medical conditions were found less likely to be low adherent to their medications compared with patients with a higher number of medications and medical conditions. This finding is consistent with previous studies [ 30 , 31 , 36 , 37 ], which higher number of medications and medical conditions resulted in low medication adherence because of medication regimen complexity, medication adverse effects, the inability of patients to afford multiple medications. A higher number of medications may also contribute to the loss of the time of administration of medications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the majority of T2DM patients were found to have a low level of adherence. This nding is consistent with an earlier study (18), but it is much higher than the other studies (14,19,37,(39)(40)(41). The study ndings indicate that a signi cant proportion of patients with comorbidity fails to achieve the expected adherence level of medications.…”
Section: Discussionsupporting
confidence: 91%
“…The nal outcome score used to categorize the medication adherence level as low adherence and high adherence was determined by computing the sum of each item scores. If the overall GMAS score ≤ 26, the patient was categorized under low adherence and patients were categorized under high adherence if the GMAS score was greater than or equal to 27 out of 33 overall maximum points (37).…”
Section: Outcome Measurementsmentioning
confidence: 99%